Proses Menyusui Dapat Mempercepat Proses Penurunan Fundus Uteri Pada Ibu Postpartum - N. Surtinah; Uswatun Khasanah; Rahayu Sumaningsih (FORUM ILMIAH KESEHATAN, 2019)
Changes in the reproductive organs in the postpartum period as a whole are called involution. One component of the involution is a decrease in the uterine fundus. This study aims to analyze the effect of breastfeeding on fundus uterine decline in post partum mothers at the West Bhakti Persada Maternity Hospital, Magetan. The study design was cross-sectional. The population in this study were all postpartum mothers who breastfeed through baby suction at the Maternity Hospital